Pendidikan Karakter di Era Modern: Telaah Pendekatan dan Metode dalam Konteks Transformasi Pendidikan - Nadia Saputri; Putri Anggalia Puspita; Anni Wulandzari; Hajizah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Character education in the modern era is a crucial foundation in shaping a generation that is not only intellectually superior, but also has strong moral, ethical and personality integrity. In the context of changing times, especially in the midst of the rapid development of digital technology and globalization that brings a variety of external influences, character education acts as a counterweight in directing moral behavior and decision-making. This study aims to identify relevant approaches and methods in implementing character education for today's generation through a literature review of various scientific journals. The results show that effective approaches in character education include value cultivation, cognitive moral development, value clarification, learning by doing, and a comprehensive approach that involves all aspects of education as a whole. Methods such as modeling, dialogue, habituation, simulation, storytelling, and integration of character values in every aspect of school activities have proven to be able to internalize these values deeply and sustainably. Furthermore, the success of character education is strongly influenced by the active involvement of various elements such as educators, parents, and the wider community, coupled with the wise use of information technology and the preservation of local wisdom values as the nation's cultural identity. The new contribution of this study lies in the mapping of character education approaches and methods that link the dynamics of the modern era with the involvement of local values, an aspect that has rarely been fully discussed in previous research. Therefore, character education that is systematically designed, structured, and sustainable is the main key in shaping a resilient, noble, and ready young generation to face complex challenges in the modern era